Laparoscopic transgastric circumferential stapler-assisted vs. endoscopic esophageal mucosectomy in a porcine model - Steinemann, Daniel; Müller, Philip C.; Sauer, Peter; Schaible, Anja; Lasitschka, Felix; Schwarz, Anne-Catherine; Müller, Beat P.; Linke, Georg R. (Endoscopy, 2017)
Background and study aims: Extensive endoscopic mucosal resection (EMR) for Barrett’s esophagus (BE) may lead to stenosis. Laparoscopic, transgastric, stapler-assisted mucosectomy (SAM) with the retrieval of a circumferential specimen is proposed. Methods: SAM was evaluated in two phases. The feasibility of SAM and the quality of specimens were assessed in eight animals. The mucosal healing was evaluated in a 6-week survival experiment comparing SAM (n = 6) with EMR (n = 6). The ratio of the esophageal lumen width (REL) at the resection level measured on fluoroscopy at 6 weeks divided by the width immediately after resection was compared. Results: In all animals, a circular mucosectomy specimen was successfully obtained, with a median area of 492 mm2 (interquartile range [IQR] 426 - 573 mm2) and 941 mm2 (IQR 813 - 1209 mm2) using a 21 mm and 25 mm stapler, respectively. In the survival experiments, symptomatic stenosis developed in two animals after EMR and in none after SAM. The REL was 0.27 (0.18 - 0.39) and 0.96 (0.9 - 1.04; P < 0.0001) for EMR and SAM, respectively. Conclusions: SAM provides a novel technique for en bloc mucosectomy in BE. In contrast to EMR, mucosal healing after SAM was not associated with stenosis up to 6 weeks after intervention.